Fluid-Induced Processes: Metasomatism and Metamorphism - Putnis, Andrew; Austrheim, H. (Wiley-Blackwell, 2011)
Metamorphism and metasomatism both involve the reequilibration of mineral assemblages due to changes in pressure, temperature and ⁄ or chemical environment. Both processes involve material transport but on different length scales, so every metamorphic reaction is metasomatic on a local scale. Fluids provide a transport mechanism which is orders of magnitude faster than solid state diffusion and induce reequilibration through dissolution of parent phases and reprecipitation of products. Chemical weathering (kaolinitization and serpentinization), and albitization are used as examples to describe the coupling between dissolution and precipitation. Albitization of feldspars in nature and in experiments is a pseudomorphic replacement which generates porosity in the albite. Porosity generation associated with interface-coupled dissolution-precipitation allows rapid material transport and together with fluid induced fracturing, is the mechanism of pervasive fluid flow through reacting crystals. Examples of metamorphic reactions in granulite-eclogite rocks illustrate the role of fluids in inducing chemical changes along fluid pathways. Microstructural criteria for a metamorphic event (i.e. change in P, T) are critically reviewed by describing the corona formed by reaction between kyanite and garnet, as well as partial replacement textures. We conclude that both corona structures and partial replacement textures are equally indicative of a metasomatic reaction (driven by a fluid-induced compositional change) as they may be of a metamorphic reaction driven by a change in P and ⁄ or T. This raises the question of the extent to which fluids play not only a catalytic role but also a thermodynamic role in determining the course of a metamorphic reaction